2022
DOI: 10.1097/iop.0000000000002190
|View full text |Cite
|
Sign up to set email alerts
|

Cemiplimab for Orbital Squamous Cell Carcinoma in 11 Cases

Abstract: To review the demographics, clinical features, and response of orbital squamous cell carcinoma treated with cemiplimab.Methods: This is a retrospective multi-institutional series. Patient characteristics, drug dosing, duration, and response to treatment were evaluated.Results: The study cohort consisted of 11 patients from 5 institutions. All patients received a regimen of 350 mg q 3 weeks and an average of 11.2 cycles (SD 5.8). No patient experienced significant side effects requiring treatment or cessation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Four patients with high tumor mutation burden (60 Mut/Mb) showed complete and durable response after a mean follow-up of 6 months, while 1 patient with low tumor mutation burden (8.1 Mut/Mb) failed. Later, Steren et al 8 reported similar results with cemiplimab for the treatment of cSCC with orbital involvement in 11 patients. Nine of 11 (82%) patients demonstrated complete response without any significant side effects.…”
Section: Discussionmentioning
confidence: 80%
“…Four patients with high tumor mutation burden (60 Mut/Mb) showed complete and durable response after a mean follow-up of 6 months, while 1 patient with low tumor mutation burden (8.1 Mut/Mb) failed. Later, Steren et al 8 reported similar results with cemiplimab for the treatment of cSCC with orbital involvement in 11 patients. Nine of 11 (82%) patients demonstrated complete response without any significant side effects.…”
Section: Discussionmentioning
confidence: 80%
“…12 Hoffmann et al 13 reported on a patient with advanced cSCC who received treatment with cemiplimab and showed stable disease (SD) that did not progress for a 19-month follow-up. Steren et al 15 reported 11 orbital SCC patients who were treated with cemiplimab, although it was not specifically mentioned how many of these patients were cSCC. Nine of 11 (82%) patients demonstrated CR without any significant side effects after a mean follow-up of 14.9 months.…”
Section: Conjunctival Squamous Cell Carcinomamentioning
confidence: 99%
“…Five of these patients went on to surgery after achieving a clinical response and the other two who had extensive prior surgery and radiation achieved a complete response without further treatment ( 65 ). A series of 11 patients with orbital SCC that would require exenteration were treated with cemiplimab and 9/11 (82%) had a CR without need for surgery, with only one patient progressing on cemiplimab and another patient entering hospice for a second cancer ( 66 ). The largest such study of 13 patients in Israel of periocular SCC with orbital invasion treated with cemiplimab showed an overall response in 9/13 (69.2%) of patients with 7/13 (53.8%) achieving a CR.…”
Section: Squamous Cell Carcinoma Of the Skinmentioning
confidence: 99%